DERIVATIZATION OF PHOTOACTIVE STRUCTURES SI(N+)/SI(P)/SI(P+) THROUGH ION-BEAM CRYSTALLIZATION - V. N. Varavka; S. N. Chebotarev; A. S. Pashchenko; V. A. Irkha (Advanced Engineering Research, 2013)
The physical and mathematical mass-transfer model of the ion-beam crystallization method is developed. The derivatization of photoactive structures Si(n+)/Si(p)/Si(p+) on 100 mm substrates through ion-beam crystallization is considered. The optimum conditions for the process: residual pressure in the growth chamber — 10−4 Pa; the substrate temperature — 550 °C; ion current density — 2 mA/cm2; acceleration voltage — 400 V; target — substrate distance — 150 mm are determined. The scanning electron microscopy data show that the grown photoactive structures have closely a faultless surface. The results demonstrate that the photoactive structures Si(n+)/Si(p)/Si(p+) offer the external quantum efficiency over 90 % in the wavelength range of 550—900 nm (spectrum AM 1.5) under the following conditions: front layer thickness Si(n+) — 100 nm; donor doping density n+ = 5∙1018 cm−3; layer thickness Si(p) — 130 μm; acceptor doping density p = 2∙1016 cm−3; layer thickness Si(p+) — 500 nm; acceptor doping density p+ = 1∙1018 cm−3.